Case Study: Development of Employee Suggestion System at OKNOPLAST Manufacturing Company as Element of Process Improvement - Męcfel, Emilia (Wydawnictwa AGH, 2024)
This case study is focused on the development of the employee suggestion system at OKNOPLAST, a window joinery company. Based on the principles of the Kaizen philosophy, this system allows employees to make suggestions for improving the company’s production processes and their work environment. In the course of the analysis, a decline in the number of suggestions that were made and a reduced rate of their acceptance were identified, which indicated the need to get to the root causes of this phenomenon using lean methodology and elements of business-process management (BPM). In response to these challenges, measures were taken that included spreading awareness among managers, promoting the employee suggestion system (ESS), training new employees, and providing technical and analytical support for process engineering; these increased the number of submitted and accepted suggestions. Visualizations of the results and transparent reports were used, which contributed to an increase in the number of submitted and successful applications. As a result, there was an increase in the acceptance rate and employee involvement in the continuous improvement process. The study showed that lean and Kaizen methods had positive impacts on the company’s organizational culture and process efficiency. The results suggested that similar solutions could be successfully adapted in other manufacturing companies regardless of the industry. The study’s conclusions underscore the importance of engaging employees and supporting their initiatives, which can be key to achieving long-term benefits and improving performance.
Decision Making in Manufacturing and Services
Keywords: Kaizen; continuous improvement; BPM